De Novo Transcriptome Assembly and Analysis of the Flat Oyster Pathogenic Protozoa Bonamia Ostreae - Chevignon, Germain; Dotto-Maurel, Aurélie; Serpin, Delphine; Chollet, Bruno; Arzul, Isabelle (Frontiers in Cellular and Infection Microbiology, 2022)
The flat oyster Ostrea edulis is an oyster species native to Europe. It has declined to functional extinction in many areas of the NE Atlantic for several decades. Factors explaining this decline include over-exploitation of natural populations and diseases like bonamiosis, regulated across both the EU and the wider world and caused by the intracellular protozoan parasite Bonamia ostreae. To date, very limited sequence data are available for this Haplosporidian species. We present here the first transcriptome of B. ostreae. As this protozoan is not yet culturable, it remains extremely challenging to obtain high-quality -omic data. Thanks to a specific parasite isolation protocol and a dedicated bioinformatic pipeline, we were able to obtain a high-quality transcriptome for an intracellular marine micro-eukaryote, which will be very helpful to better understand its biology and to consider the development of new relevant diagnostic tools.